New creatine transporter assay and identification of distinct creatine transporter isoforms in muscle. - Walzel, B; Speer, O; Boehm, E; Kristiansen, S; Chan, S; Clarke, K; Magyar, J; Richter, E; Wallimann, T (2002)
Despite the pivotal role of creatine (Cr) and phosphocreatine (PCr) in muscle metabolism, relatively little is known about sarcolemmal creatine transport, creatine transporter (CRT) isoforms, and subcellular localization of the CRT proteins. To be able to quantify creatine transport across the sarcolemma, we have developed a new in vitro assay using rat sarcolemmal giant vesicles. The rat giant sarcolemmal vesicle assay reveals the presence of a specific high-affinity and saturable transport system for Cr in the sarcolemma (Michaelis-Menten constant 52.4 +/- 9.4 microM and maximal velocity value 17.3 +/- 3.1 pmol x min(-1) x mg vesicle protein(-1)), which cotransports Cr into skeletal muscle together with Na(+) and Cl(-) ions. The regulation of Cr transport in giant vesicles by substrates, analogs, and inhibitors, as well as by phorbol 12-myristate 13-acetate and insulin, was studied. Two antibodies raised against COOH- and NH(2)-terminal synthetic peptides of CRT sequences both recognize two major polypeptides on Western blots with apparent molecular masses of 70 and 55 kDa, respectively. The highest CRT expression occurs in heart, brain, and kidney, and although creatine kinase is absent in liver cells, CRT is also found in this tissue. Surprisingly, immunofluorescence staining of cultured adult rat heart cardiomyocytes with specific anti-CRT antibodies, as well as cell fractionation and cell surface biotinylation studies, revealed that only a minor CRT species with an intermediate molecular mass of approximately 58 kDa is present in the sarcolemma, whereas the previously identified major CRT-related protein species of 70 and 55 kDa are specifically located in mitochondria. Our studies indicate that mitochondria may represent a major compartment of CRT localization, thus providing a new aspect to the current debate about the existence and whereabouts of intracellular Cr and PCr compartments that have been inferred from [(14)C]PCr/Cr measurements in vivo as well as from recent in vivo NMR studies.